2015
DOI: 10.1093/europace/euv206
|View full text |Cite
|
Sign up to set email alerts
|

Reduced residual conduction gaps and favourable outcome in contact force-guided circumferential pulmonary vein isolation

Abstract: AimsAlthough contact force (CF)-guided circumferential pulmonary vein isolation (CPVI) for paroxysmal atrial fibrillation (PAF) is useful, AF recurrence at long-term follow-up still remains to be resolved. The purpose of this study was to assess safety and efficacy of CF-guided CPVI and to compare residual conduction gaps during CPVI and long-term outcome between the conventional (non-CF-guided) and the CF-guided CPVI.Methods and resultsWe studied the 50 consecutive PAF patients undergoing CPVI by a ThermoCool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Contact force sensing catheters have allowed continuous monitoring of the CF during catheter ablation procedures. Previous studies demonstrated that the lesion size correlated well with the CF, and PV isolation with a CF sensing catheter reduced any residual conduction gaps and the incidence of PV reconnections . The present study showed that PV isolation with CF monitoring had a higher success rate of PV isolation after creating an initial circumferential ablation line.…”
Section: Discussionsupporting
confidence: 64%
“…Contact force sensing catheters have allowed continuous monitoring of the CF during catheter ablation procedures. Previous studies demonstrated that the lesion size correlated well with the CF, and PV isolation with a CF sensing catheter reduced any residual conduction gaps and the incidence of PV reconnections . The present study showed that PV isolation with CF monitoring had a higher success rate of PV isolation after creating an initial circumferential ablation line.…”
Section: Discussionsupporting
confidence: 64%
“…Optimal tissue contact during the procedure was conceptually associated with a maximal ablation efficacy, while minimized the incidence of perforation and steam pops . Since the advent of CF‐sensing technology, a majority of clinical studies had identified the beneficial effect of RF ablation implemented with CF measurement in improving primary effectiveness and safe outcomes . Data from other contemporary studies, however, provided conflicting results .…”
Section: Introductionmentioning
confidence: 99%
“…The procedural success of radiofrequency (RF) paroxysmal atrial fibrillation (AF) ablation is associated with complete and perennial pulmonary veins (PVs) isolation by adjacent transmural lesion creation. After AF ablation, PV reconnections are mainly the fact of non‐transmural lesion creating gaps of conduction in the lines, responsible for clinical recurrences . Transmurality obtention is multifactorial, and may be predicted by electrograms (EGMs) modification …”
Section: Introductionmentioning
confidence: 99%
“…After AF ablation, PV reconnections are mainly the fact of nontransmural lesion creating gaps of conduction in the lines, responsible for clinical recurrences. 1 Transmurality obtention is multifactorial, and may be predicted by electrograms (EGMs) modification. 2 There is now overwhelming proof that electrode-tissue contact force (CF) during RF application is a major determinant of RF lesions size.…”
Section: Introductionmentioning
confidence: 99%